Ecology and management of the invasive land snail Bulimulus bonariensis (Rafinesque, 1833) (Stylommatophora: Bulimulidae) in row crops - Rabelo, Marcelo Mendes; Dimase, Marcelo; Paula-Moraes, Silvana V. (Frontiers in Insect Science, 2022)
Solutions for managing the growing populations of the snail Bulimulus bonariensis (Rafinesque, 1833) in row crops, notably peanut (Arachis hypogaea L.), are urgently needed in the United States. This species has become a concern to the economy and food security for infesting commercial crops in U.S. southern states. In the present study, sampling, trapping, and management strategies were investigated to support a management program for B. bonariensis in row crops. In addition, the preference of B. bonariensis for species of row crops and weeds, used as a shelter, and snail dispersal capacity were documented. The results indicated that the ideal tools for monitoring and capturing snails are beat cloth and cardboard trap, respectively. Metaldehyde 4% bait produced effective control. Tillage was tested as an alternative cultural management tactic and produced the most promising outcomes in lowering snail populations. According to snail ecological studies, peanut and soybean are the preferred crops used as shelter over cotton and corn. Among eight common winter-growing weeds, the favored non-crop host plants are cutleaf primrose (Oenothera laciniata) and dandelion (Taraxacum officinale). The snail field population tends to increase as early spring temperatures rise, with more snails becoming trapped in warm, humid conditions but not through heavy precipitation. This study provides ecology information on B. bonariensis and validates tactics to manage this invasive species in row crops, in an IPM approach.